FORMATION OF ECO-FORESIGHT COMPETENCE IN FUTURE SPECIALISTS - Shomurotov, Bahrom Husanovich (Innovative Development in Educational Activities, 2023)
The following article is based on the need for a future modern specialist to be able to see technical and technological innovations that may occur in the future, to adapt to them and to be able to predict not only the development but also the problems that will arise, and the need to plan the solution of problems in advance. Information about foresight as one of the most modern technologies of ecological forecasting is given, the classification of foresight methods and ways of using them are described. The importance, purpose and role of future specialists during the professional activity of the eco-foresight competence is determined